2018
DOI: 10.3389/fmicb.2018.02921
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Inhibition of Anaerobic Volatile Fatty Acid Degrading Microbial Communities

Abstract: Ammonia inhibition is an important reason for reactor failures and economic losses in anaerobic digestion. Its impact on acetic acid degradation is well-studied, while its effect on propionic and butyric acid degradation has received little attention and is consequently not considered in the Anaerobic Digestion Model No. 1 (ADM1). To compare ammonia inhibition of the degradation of these three volatile fatty acids (VFAs), we fed a mixture of them as sole carbon source to three continuous stirred tank reactors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…The authors of this study observed differences in the tolerance of the different syntrophic bacteria. This study showed higher tolerance of Syntrophomonas, while Syntrophobacter decreased in abundance and was potentially replaced by so far unidentified propionate degraders under increased ammonia conditions (Bonk et al, 2018). These findings in regard to the sensitivity of the overall syntrophic community involved in the anaerobic degradation within biogas reactors need to be further investigated in future studies.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…The authors of this study observed differences in the tolerance of the different syntrophic bacteria. This study showed higher tolerance of Syntrophomonas, while Syntrophobacter decreased in abundance and was potentially replaced by so far unidentified propionate degraders under increased ammonia conditions (Bonk et al, 2018). These findings in regard to the sensitivity of the overall syntrophic community involved in the anaerobic degradation within biogas reactors need to be further investigated in future studies.…”
Section: Resultsmentioning
confidence: 81%
“…During the time of the experiment, all other incubation parameters such as temperature, pH, mixing, and feeding were kept constant and identical for the ammonium-shocked and control reactors. In other studies, the progressive increase in ammonia concentration and its monitoring over prolonged periods of time has been investigated by the addition of protein-rich feedstock (Ziganshin et al, 2013; Lv et al, 2014; Kovacs et al, 2015; Bonk et al, 2018). In these experiments, ammonia is released by the degradation of the substrate gradually and simulates a rather natural process closer to the one occurring in the commercial-scale biogas reactor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the VFAs, that with the largest proportion among the six main components of VFAs was acetic acid, which reached its maximum (894.29 mg/L) in the last period of the experiment. In addition, propionic, butyrate, and iso-butyrate acid all cumulated in the fifth stage, indicating that the bioconversion and microbial activity were relatively weaker under high ammonia concentrations [28]. Owing to the high TAN in this stage, a huge amount of VFA accumulation could be attributed to the rising TAN and FAN concentrations.…”
Section: Resultsmentioning
confidence: 99%